EFEKTIFITAS SENAM AEROBIC INTENSITAS SEDANG TERHADAP PERSEN LEMAK TUBUH DAN BERAT BADAN PADA MAHASISWI OVERWEIGHT DI JURUSAN GIZI POLTEKKES KEMENKES SEMARANG - Utaminingtyas Budiasih; Enik Sulistyowati; Ria Ambarwati; J Supadi; Meirina Dwi Larasati (JURNAL RISET GIZI, 2018)
Background  : Communicable diseases is one of the health problems causing deaths in Indonesia. To handle the problem, the government formed Posbindu-PTM which is expected to detect as early as possible non-communicable diseases. Posbindu-PTM is expected to solve the problem but its participation is still low. The success of Posbindu-PTM is influenced by various factors such as the level of knowledge, completeness of facilities and infrastructure and family support.Objective  : To determine the determinant factors of community participation in posbindu-PTM in the work area of Puskesmas Leyangan, Semarang regency. Method  : A recent survey of analytic research design it is the were cross sectional .Large in the entire household sample 107 and extraction of to be sampled taking proportionate random sampling .The data were drawn their level of participation , community knowledge , the completeness of the facilities and infrastructures and family encouragement uses a questionnaire .It is anticipated that analysis data using chi-square to bivariat and the regression of the logistics simple to multivariate .Result  : Active community participation on Posbindu-PTM 67,3% and less active 32,7%. Bivariate analysis of the relationship between the knowledge level of the community and the participation of p = 0,000, the relation of facilities and infrastructure with participation p = 0,021 and family support relationship with participation p = 0,000. Multivariate analysis of knowledge level p = 0,000 (p value 0,05), completeness of facility and infrastructure p = 0,483 (p value 0,05) and family support p = 0,162 (p value 0,05). Conclusion: The factors that influence community participation in Posbindu-PTM in Leyangan Puskesmas are knowledge level, completeness of facilities and infrastructure and family support and the most dominant is the level of knowledge.